2020
DOI: 10.2147/cmar.s254072
|View full text |Cite|
|
Sign up to set email alerts
|

<p>lncRNA TM4SF1-AS1 Activates the PI3K/AKT Signaling Pathway and Promotes the Migration and Invasion of Lung Cancer Cells</p>

Abstract: Metastasis is a crucial cause of the high mortality in patients with lung cancer. Long non-coding RNAs (lncRNAs) are emerging as important players in the development and progression of human cancers. Here, we aimed to identify metastasis-associated lncRNA and to study its roles in the migration and invasion of lung cancer cells. Materials and Methods: We screened differentially expressed lncRNAs between high-and low-metastatic lung cancer cell lines by using microarray and identified the target lncRNA TM4SF1-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…LncTM4SF1-AS1 in four GC cell lines, MKN28, AGS, MGC803 and SGC7901, was also significantly higher than that in normal gastric mucosa cells. The above results suggest that lncTM4SF1-AS1 was upregulated in GC, which is similar to that reported in the literature in NSCLC [ 9 ] and breast carcinoma [ 10 ]. In view of its upregulation in GC tissues and cells, this study selectively downregulated lncTM4SF1-AS1 in GC cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…LncTM4SF1-AS1 in four GC cell lines, MKN28, AGS, MGC803 and SGC7901, was also significantly higher than that in normal gastric mucosa cells. The above results suggest that lncTM4SF1-AS1 was upregulated in GC, which is similar to that reported in the literature in NSCLC [ 9 ] and breast carcinoma [ 10 ]. In view of its upregulation in GC tissues and cells, this study selectively downregulated lncTM4SF1-AS1 in GC cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…TM4SF1-AS1 is a 754-bp lncRNA that was first identified and found in the screening of lncRNAs related to the metastasis of NSCLC [ 19 ]. An in vitro study of NSCLC revealed that it is highly expressed in non-small cell lung cancer lines and promotes invasion and metastasis of carcinoma cells [ 9 ]. In high-throughput RNA sequencing, it was also found that lncTM4SF1-AS1 was significantly increased in colorectal carcinoma regulated and induced by hypoxia [ 20 ], and its function is still under exploration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PI3K/AKT signaling pathway has been reported to be involved in the migration and invasion of various tumor types. 18 , 19 Therefore, we hypothesized that LukS-PV might inhibit the activation of the PI3K/AKT signaling pathway by downregulating TNNC1. To verify this hypothesis, Western blot analysis was undertaken to detect the expression of these pathway proteins.…”
Section: Resultsmentioning
confidence: 99%